The Semiotics of Color in the Poetry of Ibn Waki` al-Tannisi (393 AH) - Shafi Alifan, Sadoun Ismaell (Journal of Tikrit University for Humanities, 2023)
Semiotics, while referred to by several words in ancient and modern Arab philosophy, ultimately converges in its contemporary understanding. Notably, the deliberate use of color semiotics by poets serves as a significant signal. Hence, Bin Waki` al-Tanisi, the poet, is widely regarded as a highly innovative figure in the realm of color use within his poetic compositions. He adeptly selects hues that align with the intended significance he seeks to convey via his verses. The poet in question has garnered significant scholarly attention and acclaim for the aesthetic qualities of his poetry, characterized by its beauty, linguistic elegance, and mellifluousness. The user's inquiry pertains to the selection process and the attributed significance in order to analyze the semiotics and the consequential effectiveness of this proficient use. The individual demonstrated proficiency in using the color red, including its many connotations, semiotic implications, and psychological effects on the reader. This aptitude extends to the other colors previously discussed. The study has yielded several findings, with one of the most significant being the prominent presence of color in Ibn Waqa's Divan. The poet demonstrated meticulous attention to detail in his depiction of poetic imagery, providing explicit descriptions of colors and utilizing words that conveyed the essence of the poetic scene. The poet used the use of colors to depict the aesthetic and virtuous qualities of women, as well as to illustrate the embellishment associated with them. Additionally, the poet provided intricate descriptions of wine and its accompanying rites, emphasizing the vividness of these depictions. Furthermore, the poet elaborated on the arrival of spring, highlighting the multitude of colors found inside flowers during this season.